Public Debt and Total Factor Productivity - Leo Kaas (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper explores the role of public debt and fiscal deficits on factor productivity in an economy with credit market frictions and heterogeneous firms. When credit market conditions are sufficiently weak, low interest rates permit the government to run Ponzi schemes so that permanent primary deficits can be sustained. For small enough deficit ratios, the model has two steady states of which one is an unstable bubble and the other one is stable. The stable equilibrium features higher levels of credit and capital, but also a lower interest rate, lower total factor productivity and output. The model is calibrated to the US economy to derive the maximum sustainable deficit ratio and to examine the dynamic responses to changes in debt policy. A reduction of the primary deficit triggers an expansion of credit and capital, but it also leads to a deterioration of total factor productivity since more low-productivity firms prefer to remain active at the lower equilibrium interest rate.
Keywords: D92; E62; H62; 330; credit constraints; unbacked public debt; dynamic inefficiency; sustainable deficits